Pengaruh Brand Ambassador, Discount Dan Review Produk Scarlett Terhadap Keputusan Pembelian Di Tiktok Shop - Zahra Sari Safira; Ronny Malavia Mardani; M. Tody Arsyianto (E-JRM : Elektronik Jurnal Riset Manajemen, 2023)
Abstract This study aims to determine and analyze the influence of Brand ambassador variables, Discounts and Scarlett product reviews on Purchase Decisions on Tiktok Shop. This research uses a case study on students of the Faculty of Economics and Business, Islamic University of Malang, class of 2019 who were selected by accidental sampling. Determination of the number of samples using the malholtra formula and obtained the results of 90 respondents. Data collection was carried out using Questionnaires. The data analysis methods used in this study are Instrument Test (validity test and reliability test), Normality Test, Classical Assumption Test (multicollinearity test and heteros kedasticity test), Multiple Linear Regression Analysis, Statistical Test (t test), and Determination Coefficient Test (Adjusted R2) and Analysis process using SPSS 22. The results stated that the variables Brand ambassador, Discount and Review affect purchasing decisions. Keywords: Brand Ambassador, Discount, Review, Purchase Decision